1974
DOI: 10.1073/pnas.71.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inhibition of Eukaryotic Protein Synthesis by Trichothecene Fungal Toxins

Abstract: The 12,13-epoxytrichothecenes, a group of sesquiterpenoid fungal antibiotics, inhibit protein syn-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
121
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 206 publications
(126 citation statements)
references
References 12 publications
5
121
0
Order By: Relevance
“…3,15-didesacetylcalonectrin). Thus esterification of the hydroxyl at R3 appears to induce an increased I-type response, in agreement with the work of Cundliffe et al (1974), where it was suggested that the presence of an oxygen-containing substituent at R3 is necessary to produce such an effect.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…3,15-didesacetylcalonectrin). Thus esterification of the hydroxyl at R3 appears to induce an increased I-type response, in agreement with the work of Cundliffe et al (1974), where it was suggested that the presence of an oxygen-containing substituent at R3 is necessary to produce such an effect.…”
Section: Discussionsupporting
confidence: 88%
“…4e), and the 'run off' was complete when the concentration of diacetoxyscirpenol was lowered further (1-10g/ml). Total 'run off' was also achieved by adding 15-acetoxyscirpendiol at 1-5,ug/ml, or T-2 toxin, observed by Cundliffe et al (1974) to be an I-type inhibitor (Schindler, 1974), at any concentration between 1 and 150jug/ml (Fig. 4h).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations